From Aristocratic to Ordinary: Shifting Modes of Elite Distinction - Friedman, Sam; Reeves, Aaron (American Sociological Review, 2020)
How do elites signal their superior social position via the consumption of culture? We address this question by drawing on 120 years of “recreations” data ( N = 71,393) contained within Who’s Who, a unique catalogue of the British elite. Our results reveal three historical phases of elite cultural distinction: first, a mode of aristocratic practice forged around the leisure possibilities afforded by landed estates, which waned significantly in the late-nineteenth century; second, a highbrow mode dominated by the fine arts, which increased sharply in the early-twentieth century before gently receding in the most recent birth cohorts; and, third, a contemporary mode characterized by the blending of highbrow pursuits with everyday forms of cultural participation, such as spending time with family, friends, and pets. These shifts reveal changes not only in the contents of elite culture but also in the nature of elite distinction, in particular, (1) how the applicability of emulation and (mis)recognition theories has changed over time, and (2) the emergence of a contemporary mode that publicly emphasizes everyday cultural practice (to accentuate ordinariness, authenticity, and cultural connection) while retaining many tastes that continue to be (mis)recognized as legitimate.